Modelos de gestão de energia para pequenas micro redes fotovoltaicas no contexto colombiano - Hernandez, Alejandro Sallyth Guerrero (2021)
A developing country that does not have adequate energy solutions undoubtedly experiences adverse effects in terms of its competitiveness, economic, and social development. In recent decades the electrical power system has evolved into low-scale microgrids that integrate distributed power resources, loads, power converters, and grid components stably, working in grid-connected or island mode. This thesis focuses on the study of adaptable energy management systems for microgrids to coordinate generation, demand, and storage, given the needs of the user in the Colombian context. The first case study considers the non-interconnected zones (ZNI), where the primary source of electrical energy in these communities is diesel generators, which are expensive and do not respect the environment. The case study objective is to propose a model to an energy system able to reduce the consumption of this fossil fuel in the Colombian ZNI. The technical and economical implementation of a small-scale photovoltaic system with and without a hybrid energy storage system (HESS) connected to the grid is proposed based on Colombian regulation’s incentive policy. A mixed-integer nonlinear programming optimization model (MINLP) was developed, including the storage costs of a lead-acid battery and a supercapacitor. This model allows to analyze the benefits of the electric tariff and maximize the income of the generation by photovoltaic system. This study’s conclusions offer policy suggestions and economic incentives to improve the use of renewable energy sources in Colombia’s ZNIs. It also serves as a precedent that can be implemented in other developing countries. The second case introduces the concept of agrivoltaic as a dual-purpose land-use solution (power generation and planting). An analysis is carried out to evaluate the installation of photovoltaic systems elevated at a considerable height from the ground, and below them, industrial cassava is grown. For such installation, a mixed-integer linear optimization model (MILP) is developed to optimize the proposed microgrid operation while managing the stored energy in a battery bank, reducing the heat absorbed from the electricity grid, and, in case of a surplus, exporting it for sale. The results show that the producer will obtain a double benefit: the sale of energy throughout the year and the profit generated by industrial cassava, which contributes to preserving food security and satisfying the growing electricity demand.